Academic bullying as a racialized phenomenon in STEM higher education: Centering the experiences of Asian international doctoral students - Wang, Peiwen (Journal of International Students, 2024)
While students of color’s experiences of academic bullying from their advisors have been documented in the literature (e.g., Moss & Mahmoudi, 2021), little is known regarding the role that race plays in the normalization and perpetuation of academic bullying within higher education. Utilizing Asian critical theory (AsianCrit) as both the theoretical and analytical lens, this phenomenological study centers five STEM Asian international doctoral students’ experiences of academic bullying through semi-structured interviews. It is found that racialized academic bullying is operationalized by a) legitimizing exploitation through racializing discourses; b) maintaining White supremacy across transnational contexts; and c) intersecting systems of oppression. Implications and recommendations are offered as to what stakeholders can do collectively to address racialized academic bullying towards minoritized students and to combat systemic inequities and oppression.